Willingness to pay for dengue vaccine among parents of elementary school students in Denpasar - Indraswari, Ni Luh Astri; Wirawan, Dewa Nyoman; Kardiwinata,, Made Pasek; Januraga, Pande Putu (Public Health and Preventive Medicine Archive, 2021)
Background and purpose: The incidence of Dengue Hemorrhagic Fever (DHF) in Bali, especially in Denpasar, remains high. Efforts to eradicate mosquito nests have been carried out but did not give a significant reduction in the incidence number. The dengue vaccine is now available and can be a way of prevention. The dengue vaccine has not been included in the mandatory immunization program by the government so people who want to get vaccinated have to pay for it by themselves. This study aims to determine the relationship between socio-demographic factors and perceptions with the willingness to pay for the dengue vaccine among parents of elementary school students in Denpasar. Methods: This study used a cross sectional design involving 100 mothers of students from grade 3 to grade 6 at Dauh Puri 5 Elementary School and Dauh Puri 6 Elementary School who were selected with systematic random sampling. Data collected included education level, income, respondents’ perceptions and willingness to pay for dengue vaccine. Data were collected by interview using a questionnaire, the results were analyzed using a multivariate logistic regression. Results: The average willingness of parents to pay for the dengue vaccine per dose was IDR 131,170. Percentage of respondents who were willing to pay for the dengue vaccine was 31%. The results of analysis showed that variables associated with parents’ willingness to pay for the dengue vaccine were education level (OR=4.06; 95%CI: 1.19-13.76), perceived susceptibility (OR=1.59; 95%CI: 0.58-4.37) and perceived benefits (OR=2.60; 95%CI: 1.00-6.81). Conclusion: Parents’ willingness to pay for the dengue vaccine remains very low compared to the current price of vaccine per dose. The government needs to provide subsidies so that the dengue vaccine can be included in the national immunization program and be accessed by all people. Further research is needed with a broader scope and more varied population’s characteristics to obtain a willingness to pay value that can represent society in general.